2022
DOI: 10.1007/s40497-022-00308-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding entrepreneurial vision for growth, innovation and performance in Kenya’s leather industry

Abstract: While entrepreneurial orientation’s role in determining performance of businesses has been empirically established, studies from Africa or an industry-ecosystem perspective have been scarce. Furthermore, the significance of an entrepreneur’s vision is often acknowledged but little studied in relation to entrepreneurial outcomes. This study explored vision for growth as an individual entrepreneurial disposition and its relationship with innovation and performance outcomes among industry actors. The study collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…As shown in Table 5, zero is within the lower and upper bounds that indicate marketing innovation does not significantly mediate the relationship between entrepreneurs' competency and MSME growth. This result is consistent with the finding reported by Kamuri [17]. Thus, marketing innovation is not playing a mediating role that leaves competency as the sole direct influencer of enterprise growth.…”
Section: Mediated Effectsupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Table 5, zero is within the lower and upper bounds that indicate marketing innovation does not significantly mediate the relationship between entrepreneurs' competency and MSME growth. This result is consistent with the finding reported by Kamuri [17]. Thus, marketing innovation is not playing a mediating role that leaves competency as the sole direct influencer of enterprise growth.…”
Section: Mediated Effectsupporting
confidence: 92%
“…For example, Jung and Shegai [16] found that marketing innovation has a direct and indirect effect on firm performance. Regarding the mediating effect of innovation, Kamuri [17] claimed that innovation does not mediate the association between competency and enterprise performance. Taleb et al [18] also conducted a study and found that entrepreneurial resources can significantly affect innovation capability.…”
Section: Introductionmentioning
confidence: 99%
“…From the coding process, four themes concerning vision attributes, vision content, vision communication and sustainability performance emerged. The attributes of effective vision statements are brevity, clarity, future orientation, stability, challenges, abstractness and an ability to inspire, which have been widely endorsed by scholars as effective vision attributes, e.g., [125][126][127][128][129][130][131][132][133][134][135]. In terms of vision content, there are several content imageries supporting this theme, including those related to motive, venture growth, sales, leadership and stakeholder satisfaction imageries.…”
Section: Cutting-edge Knowledge On Sustainability Organizational Visionmentioning
confidence: 99%